ANALISIS HUBUNGAN ANTAR KAPABILITAS PEMANUFAKTURAN - Soni Kurniawan, Ignatius (Widya Warta, 2012)
This research adopted Amoako-Gyampah and Meredith’s research on cumulative capabilities (2007). It aimed to examine the relationship among manufacturing capabilities (flexibility, quality, delivery, and low cost), as well as to find out whether or not the quality was a foundation for the development of cumulative capabilities. The sample of the research was manufacture firms located in Jababeka Industrial Estate, West Java. The sampling was conducted by applying non-probability method with a purposive sampling technique. The questionnaires processed were 104 in number; 79 of which were obtained from mail survey and 25 from e-mail survey. The finding showed that there was no negative correlation among the manufacturing capabilities, meaning that there was no trade-off in the development of capabilities. The finding also confirmed that the quality was a foundation for the development of cumulative capabilities.